Right hepatic artery pseudoaneurysm caused by stone extraction–related trauma during endoscopic retrograde cholangiopancreatography: a case report - Ou, Wenjie; Han, Xu; Tan, Ruyi; Huang, Yan; Xiao, Xiang (Frontiers in Medicine, 2025)
Hepatic artery pseudoaneurysm (HAP) is a rare but potentially fatal complication of endoscopic retrograde cholangiopancreatography (ERCP), often misdiagnosed due to its nonspecific presentation. We report a case of a 72-year-old male with choledocholithiasis who developed progressive biliary hemorrhage following ERCP. Initial conservative treatment and placement of a fully covered metal biliary stent failed to control the bleeding. The patient subsequently presented with hemorrhagic shock and significant hemoglobin decline. Computed tomography angiography (CTA) and digital subtraction angiography (DSA) revealed a ruptured right HAP, which was successfully managed by transcatheter arterial embolization (TAE). Detailed retrospective analysis of imaging findings and intraoperative procedures indicated that the HAP likely resulted from iatrogenic vascular injury to the right hepatic artery adjacent to the remnant cystic duct, caused by mechanical trauma during stone retrieval maneuvers. This case highlights the need for early recognition of vascular injury as a source of post-ERCP bleeding, particularly when bleeding persists despite standard endoscopic management. Timely use of CTA and DSA is essential for accurate diagnosis, and TAE offers a safe and effective treatment option.